Basic mechanism of button battery ingestion injuries and novel mitigation strategies after diagnosis and removal. (9th November 2016) - Jatana, Kris R.; Rhoades, Keith; Milkovich, Scott; Jacobs, Ian N.
Abstract : Objectives/Hypothesis: Button battery (BB) injuries continue to be a significant source of morbidity and mortality, and there is a need to confirm the mechanism of injury for development of additional mitigation strategies. Study Design: Cadaveric piglet esophageal model. Methods: Lithium, silver oxide, alkaline, and zinc–air BBs were placed in thawed sections of cadaveric piglet esophagus, bathed in normal saline. Severity of gross visual burn, pH, and temperature were recorded every 30 minutes for 6 hours. In other esophageal tissue specimens, the lithium BB was removed after 24, 36, and 48 hours and the site was irrigated with either 0.25% or 3% acetic acid. Separately, ReaLemon® juice, orange juice, Coke®, Dasani® water, Pepsi®, and saline were infused over a vertically suspended esophagus with a CR2032 lithium battery every 5 minutes for 2 hours while tissue temperature and pH were measured. Results: A gradual rise in tissue pH and minimal change in temperature was noted for all BBs. ReaLemon® and orange juice applied every 5 minutes were most effective at neutralization of tissue pH with minimal change in tissue temperature. After BB removal (24, 36, 48 hours), irrigation of esophageal tissue specimens with 50–150 mL 0.25% acetic acid neutralized the highly alkaline tissue pH. Conclusions: BB appear to cause an isothermic hydrolysis reaction resulting in an alkaline caustic injury. Potential new mitigation strategies include application of neutralizing weakly acidic solutions that may reduce esophageal injury progression. Level of Evidence: NA Laryngoscope, 127:1276–1282, 2017